Digital Readiness Configurations of Bandung MSMEs: An fsQCA Approach - Zahwa Fitria Gumilang (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Digital transformation has become a national priority in Indonesia’s Industry 4.0 agenda; however, empirical evidence on how MSMEs achieve digital readiness remain limited. This study addresses this gap by examining the configurational drivers of digital readiness using INDI 4.0 data from 16 MSMEs. Using fuzzy-set Qualitative Comparative Analysis (fsQCA), all five INDI pilars, including strategy and management (S), people and culture (O), technology (T), operations (P), and products and services (R), were calibrated using the direct method, assessed for necessity, and analyzed for sufficiency through truth tables and Boolean minimization. Results show that people and culture (O) and products and services (R) are necessary conditions for high digital readiness. Two equifinal pathways are sufficient for achieving the outcome. The dominant configuration, O·P·R → Y, indicates that readiness is primarily enabled by strong human capability, operational digitization, and market-facing digitalization, even without formalized management processes or advanced technologies. A secondary bottom-up pathway, S·O·T·R → Y, suggests that MSMEs may still achieve readiness under weak managerial formalization if people capabilities, basic technologies, and digital customer engagement are present. These findings offer practical implications: MSMEs should prioritize developing people capabilities and customer-focused digital services, followed by quick operational digitization wins before gradually strengthening strategic processes and technology sophistication. This study also extends the application of INDI 4.0 by demonstrating its suitability for small-N configurational analysis.